Cardiopulmonary and hemodynamic responses to Baduanjin exercise and cycle ergometer exercise among chronic heart failure patients: a comparison - Chen, Xiankun; Hu, Xiaoyue; Olson, Thomas P.; Qiu, Yaqi; Zhu, Huiying; Wen, Zehuai; Cai, Huayang; Lu, Weihui; Jiang, Wei (Frontiers in Physiology, 2025)
ObjectiveBaduanjin is a traditional Chinese exercise and serves as an alternative to conventional cardiac rehabilitation in China. In this study, we compare the cardiopulmonary and hemodynamic responses of Baduanjin to those of cycle ergometer exercise in chronic heart failure patients.MethodsFor this cross-sectional study design, following baseline data collection, participants underwent a series of tests including impedance cardiography (ICG) and a maximal cardiopulmonary exercise test (CPET) to determine peak exercise capacity. Participants then engaged in 9-min of Baduanjin exercise. The average oxygen consumption (EqualVO2) during Baduanjin was calculated. Participants then engaged 9 min of constant-load cycling at 60 rpm at an intensity which elicited the EqualVO2. Cardiopulmonary and hemodynamic data were measured continuously during both Baduanjin and cycling exercise.ResultsA total of 30 participants were included. Although Baduanjin and cycling exercise showed similar VO2 levels (8.2 ± 1.3 vs. 8.4 ± 1.4, p = 0.339, respectively), there was a bimodal distribution during Baduanjin exercise compared to a unimodal distribution during cycling exercise. Compared to conventional cycling, Baduanjin demonstrated lower respiratory burden which is associated with greater ventilatory efficiency as evidenced by lower respiratory rate values (p = 0.003), minute ventilation (p < 0.001), end-tidal carbon dioxide pressure (p < 0.001), and minute ventilation to carbon dioxide production ratio (p < 0.001). In terms of hemodynamic response, Baduanjin is demonstrated significantly lower cardiac output (p = 0.017) and elevated arterial-venous oxygen difference (p = 0.036).ConclusionOur study offers novel insight into the cardiopulmonary and hemodynamic differences between Baduanjin and cycling when performed at consistent intensity levels. Baduanjin demonstrates an intermittent intensity pattern and increased peripheral oxygen utilization, which is attributed to more pronounced muscle activation. Furthermore, Baduanjin has been linked to a reduction in both cardiac and respiratory burdens.